A cost-utility and budget impact analysis of long-acting insulin analogues, (determir, glargine and degludec) for the treatment of adults with T1DM in South Africa - Verryn, Mark (Unknown, 2024)
Background: Type 1 Diabetes Mellitus (T1DM) is a life-threatening condition that is managed with administered insulin. Intermediate- to long-acting insulin represents the basal insulin constituent of the total insulin used in treating T1DM and has received much research and development over the years. In South Africa, intermediate-acting Neutral Protamine Hagedorn (NPH) insulin has been the mainstay basal insulin recommended in the public sector. Newer (ultra) long-acting insulin analogues, however, have subsequently been approved for use. Costutility and budget impact analyses of the newer long-acting insulin analogues detemir, glargine and degludec have yet to be performed in the South African public health sector context. Methods: A systematic search for clinical evidence was performed to inform the economic evaluation. A cost-utility analysis was carried out utilising Markov modelling. Seven comparators were modelled representing the various insulin types and treatment regimens. For each comparator, three Markov states were created, one in which no complications occurred and another two states representing nocturnal and daytime hypoglycaemic events respectively. Three scenarios were modelled in order to capture the variable rates of complications reported in the clinical evidence. Quality-Adjusted Life Years per patient year was the health outcome utilised. Costs were included as South African Rands and then converted to United States dollars. A cost-effectiveness threshold range appropriate for the South African context was used to assess value for money. Thereafter, a budget impact analysis was conducted. Results: Three systematic reviews were identified in the systematic search for inclusion in this study. Subsequently, three scenarios were modelled in order to capture the clinical significance identified in the three systematic reviews. All three models favoured NPH insulin over the alternatives, as NPH insulin dominated most other insulins, barring insulin detemir, insulin glargine-U300 and insulin degludec. Insulin detemir was the most cost-effective option of the alternatives to NPH insulin (ICER of 10,783.75 USD/QALY). However, insulin detemir was still not cost-effective in relation to South Africa's cost-effectiveness threshold (CET 1,175 - 8,909 USD/QALY). The NPH insulin twice daily regimen was also found to dominate the NPH once daily regimen. Conclusions: The status quo of NPH insulin in the management of T1DM in adults remains the most cost-effective option for the South African public health sector. Further research and consideration could be made for the use of NPH insulin twice daily, as opposed to once daily.